(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The study reveals the mechanisms of enterprise sustainability in the digital age through the integration of AI, ESG principles, and hybrid methodologies at the stages of the life cycle (from inception to rebirth). It demonstrates how resilient ecosystems turn crises into growth opportunities.